Social network site addiction, sleep quality, depression and adolescent difficulty describing feelings: a moderated mediation model - Jiale Wang; Ning Wang; Pingfan Liu; Yang Liu (BMC Psychology)
Abstract Background and objectives Social network site addiction is strongly correlated with sleep quality among adolescents. However, the underlying mechanisms driving these relationships require further exploration. This study aims to supplement the understanding of the psychological mechanisms linking social network site addiction and sleep quality by investigating depression as a mediating factor and difficulty describing feelings as a moderating factor. Methods A self-report survey was conducted with 1,670 adolescents in China, assessing social network site addiction, sleep quality, depression, and difficulty describing feelings. Descriptive and correlational analyses were performed on these variables, followed by the construction of a moderated mediation model. Results Social network site addiction was significantly positively correlated with sleep quality, depression, and difficulty describing feelings among adolescents. Difficulty describing feelings was also significantly positively correlated with depression. Depression partially mediated the relationship between social network site addiction and sleep quality, while difficulty describing feelings intensified the relationship between social network site addiction and depression. Conclusion This study further elucidates the psychological mechanisms linking social network site addiction and sleep quality in adolescents. Depression acts as a mediating factor, while difficulty describing feelings strengthens the relationship between social network site addiction and depression. These findings highlight the role of difficulty describing feelings in the interplay between social network site addiction and sleep quality, offering valuable insights for a more comprehensive understanding and targeted interventions aimed at improving sleep quality in adolescents.